A door-to-door travel time approach for evaluating modal competition of intercity travel: A focus on the proposed Dallas-Houston HSR route. (October 2018) - Zhao, Yun; Yu, Hongbo
Highlights: A door-to-door travel time accessibility evaluation approach. New city-pair-specific catchment area delineation method that factors in modal competition. Evaluate the proposed Dallas-Houston HSR project using the proposed door-to-door approach. Apply an RGB mixing scheme to visualize detailed spatial patterns of catchment areas in the Dallas-Houston HSR corridor.